0536 Association of a Novel EEG Biomarker of Sleep Depth with Sleep Disordered Breathing in Adolescents. (25th May 2022) - Ricci, Anna; He, Fan; Calhoun, Susan; Fang, Jidong; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward; Younes, Magdy; Fernandez-Mendoza, Julio
Abstract: Introduction: The odds ratio product (ORP) provides a standardized, continuous measure of sleep depth that ranges from 0 (deep sleep) to 2.5 (full wakefulness). ORP has been shown to increase during adolescence, representing the decline in sleep depth that occurs during this developmental period. In adults, higher ORP has been associated with sleep disordered breathing (SDB), including obstructive sleep apnea (OSA), while there have been no studies in youth. We aimed to determine the association of ORP with SDB in adolescents. Methods: We extracted ORP from the sleep EEG of 261 typically developing adolescents aged 12-23y (median 16y) from the Penn State Child Cohort. Higher ORP during rapid eye movement (REM) and non-REM sleep indicates less deep sleep, while higher ORP-9 (i.e., average ORP in the 9-seconds following non-REM cortical arousals) indicates greater arousability. We used general linear models, adjusted for sex, age and race/ethnicity, to examine mean differences in ORP metrics among clinically meaningful groups of SDB based on the apnea/hypopnea index (AHI) consisting of no SDB (AHI<2 and no snoring, n=100), primary snoring (AHI<2 and snoring, n=75), 2≤AHI<5 (n=64), and AHI≥5 (n=22). Results: Adolescents with primary snoring or 2≤AHI<5 did not significantly differ in ORP metrics from those without SDB (all p≥0.12). Adolescents with AHI≥5 had higher ORP-NREM compared to those without SDB, with primary snoring or with 2≤AHI<5 (all p≤0.01), while ORP-REM was significantly higher compared to those without SDB (p=0.02). ORP-9 was significantly greater in adolescents with AHI≥5 compared to those with no SDB (p<0.01) and those with primary snoring (p=0.02), but not when compared to those with 2≤AHI<5 (p=0.07). Conclusion: Our data suggest that adolescents with OSA experience lower REM and non-REM sleep depth/intensity (higher ORP) compared to those without SDB. In addition, these adolescents experience a slower progression back to deep sleep following cortical arousals (higher ORP-9), which suggests they remain in a high arousability state and, thus, are more likely to repeat arousals. Commensurate with previous studies in adults, our data show that ORP is a useful sleep EEG biomarker able to capture decreased sleep depth in adolescents with OSA. Support (If Any): National Institutes of Health (R01MH118308, UL1TR000127)